FAKTOR KONVERSI LIMBAH PEMANENAN KAYU HUTAN TANAMAN DAN RENDEMEN PENGOLAHAN SERPIH KAYU - Soenarno; Wesman Endom (Jurnal Penelitian Hasil Hutan, 2016)
Timber harvesting in forest plantations of PT Korintiga Hutani was undertaken using length limitation of 4.10 m and minimum diameter of 10 cm. These limitations have created numerous trunk wastes in the field. Harvesting efficiency improvement is being considered by converting the wastes into wood chips. However, the company has to pay a provision of forest resources to the government for each volumetric unit (m³) of the converting wood wastes. This paper examines conversion factors for estimating conversion values from staple meter (Sm) or weight (ton) into m³ of akasia (Acacia mangium), eukaliptus (Eucalyptus pellita) and waru (Hibiscus similis). Results show that conversion value of 1 Sm A. mangium wood waste is equal to 0.35 m³, or 1 ton of the same waste is equal to 1.98 m³; conversion value of 1 Sm E. Pellita is equal to 0.48 m³, or 1 ton of the waste is equal to 1.41 m³. Conversion value for 1 Sm H. similis is equal to 0.34 m³, or 1 ton of the waste is equal to 1.95 m³. Processing recovery of wood waste into chips is 94% for A. mangium and E. pellita while recovery of H. similis is 90%. Hence, conversion factor of wood chips in relation with the required waste is 1 Sm chips = 0.38 m³ wood waste or 1 ton chips = 2.09 m³ wood waste for A. mangium. Conversion factor for E. pellita is 1 Sm chips = 0.38 m³ wood waste or 1 ton chips = 1.51 m³ wood waste; conversion factor for H. similis is 1 Sm chips = 0.39 m³ wood waste or 1 ton chips = 2.16 m³ wood waste.